Smart Home Automation System based on Arduino - Bouzid Mohamed Amine; Chaib Fatima Zohra; Hamani Ilyes; Aid Lahcen; Allaoui Tayeb (Institute of Advanced Engineering and Science, 2018)
Intelligent home environments are environments that attempt to ease the user's life in different ways and make it more comfortable using the technology. This paper present the principle of realizing a home control interface based on an. Arduino UNO R3 board equipped with a programmable ATmega328 microcontroller. The sketch to be uploaded to the Arduino is written in C language. A desktop application was created in C # language to communicate with the Arduino via the serial port, thus facilitating repetitive tasks such as lighting control, opening / closing doors. A temperature / humidity sensor, an alarm (motion sensor + buzzer), garden lighting and automatic control of the TV via an IR receiver + IR transmitter have been added without forgetting manual control